Use of Palm Oil Boiler Bottom Ash as Replacement Materials in Concrete Mix - SHEA MING, TAN; Ahmad Jeni, Mohamad Luthfi; Kosnin, Hilmi; Osman, Mohamad Hairi (Progress in Engineering Application and Technology, 2022)
Lightweight concrete is widely implemented in the construction industry to replace conventional concrete due to the high self-weight. Furthermore, the waste that produced from palm oil industry could be used as the material in concrete mixture to partially replace with the fine aggregate to solve the problem of resource depletion. The used of palm oil boiler bottom ash is the suitable fine aggregate replacement material to produced lightweight aggregate concrete. The objective of this research is to study on the performance of the lightweight concrete that using the bottom ash in the concrete mix compared to the conventional concrete. This research also important to identify the optimum percentage of palm oil boiler bottom ash that was replaced in the concrete. The samples sized with 100mm x 100mm x 100mm with the percentage of fine aggregate replacement are 10%, 20% and 30%. The mechanical properties testing methods that carried out in this research were slump test, water absorption test and compression test. At the end of the research, the optimum percentage of palm oil boiler bottom ash that was replaced in the concrete mixture is 20%. The concrete that produced had high compression strength compared to the conventional concrete.